2008
DOI: 10.1590/s0004-27302008000400013
|View full text |Cite
|
Sign up to set email alerts
|

Contribuição da apnéia obstrutiva do sono para o estresse oxidativo da obesidade

Abstract: RESUMOObjetivo: O objetivo do trabalho foi verificar a influência da apnéia obstrutiva do sono (AOS) sobre o estresse oxidativo da obesidade e o efeito do pressão positiva de vias aéreas (CPAP) nestes pacientes. Métodos: Os pacientes com IMC 30 kg/m 2 foram divididos em: a) grupo 1: dez indivíduos sem AOS; b) grupo 2: dez portadores de AOS que não fizeram o uso do CPAP; e c) grupo 3: nove portadores de AOS que fizeram uso do CPAP durante dois meses. Resultados: O grupo 3 apresentou, após o uso do CPAP, redução… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 32 publications
1
5
1
5
Order By: Relevance
“…Lima et al 17 observed the same hypoxic effect in patients with sleep apnea compared to healthy individuals, and similar data were obtained by Peled et al 12 .…”
Section: Discussionsupporting
confidence: 74%
“…Lima et al 17 observed the same hypoxic effect in patients with sleep apnea compared to healthy individuals, and similar data were obtained by Peled et al 12 .…”
Section: Discussionsupporting
confidence: 74%
“…[31][32][33] In analyzing the BQ scores, we found that the individuals with obesity participating in the multidisciplinary preoperative preparation program for bariatric surgery at Hospital de Clínicas -Unicamp were at a high risk (80.34%) of developing OSAS, versus 19.66% at low risk, thus confirming that obesity is a disease clearly identified as a risk factor for the development of OSAS. Pinto et al, 34 pointed out controversy as to which are the most significant predictive parameters of obesity leading to this association.…”
Section: Discussionmentioning
confidence: 67%
“…1,28 In OSAS, apnea and hypopnea lead to hypoxia and hypoxia-reoxygenation states, which, in turn, causes an inflammatory process and oxidative stress and, in combination with obesity, favors the formation of atheroma plaques. [29][30][31] In our study, we found that 53.8% of obese individuals have systemic arterial hypertension (SAH).…”
Section: Discussionmentioning
confidence: 99%
“…Higher BMI is associated with increased oxidative stress, independently of other parameters such as OSA [34]. …”
Section: Discussionmentioning
confidence: 99%